Amino molding plastic particle and preparation method thereof

Through the synergistic effect of amino-terminated acrylic modified amino resin and thiolated corn straw, a crosslinking network structure with high crosslink density is formed, which solves the problem of insufficient dimensional stability and mechanical properties of traditional molding materials, and achieves the preparation of molding materials with low shrinkage and high mechanical properties.

CN119735914AInactive Publication Date: 2025-04-01JINING GAOXING TIMBER PROD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411990787.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional amino resins are prone to produce a large shrinkage rate during the curing process, resulting in poor dimensional stability of the molded material and low interface compatibility with the reinforced filler, which limits the improvement of the mechanical properties of the molded material.

Method used

By using amino-terminated acrylic modified amino resin and thiolated corn stalks to form a crosslinking network structure with high crosslink density, the compatibility and mechanical properties of the amino resin and corn stalks are improved.

Benefits of technology

It realizes the low shrinkage, high bending strength and high impact strength of molded materials, significantly improving its dimensional stability and mechanical properties, and is suitable for areas with high precision and high strength requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223603870000101
    Figure BDA0005223603870000101
Patent Text Reader

Abstract

The invention relates to the technical field of plastics, in particular to amino molding plastic particles and a preparation method thereof. The preparation method of the amino molding plastic particles comprises the following steps: synthesizing amino-terminated acrylic acid, and preparing modified amino resin; carrying out pretreatment and sulfhydrylation modification on the corn straws; mixing and kneading the sulfhydrylated corn straws and the modified amino resin, drying and grinding to obtain amino molding plastic particles. According to the present invention, through the synergistic effect of the amino-terminated acrylic acid modified amino resin and the sulfhydrylated corn straw, the prepared molding compound has characteristics of low shrinkage, high bending strength, high impact strength, excellent dimensional stability and excellent mechanical property, is suitable for the field with high precision and high strength requirements, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, and in particular to amino molding plastic particles and a preparation method thereof. Background Art

[0002] Molding plastics are an important type of thermosetting plastics, which are widely used in electronics, electrical appliances, automobiles, construction and other fields, especially in situations where high precision and high strength are required. However, traditional molding plastics have certain deficiencies in mechanical properties, dimensional stability and environmental friendliness, which limits their further application in high-performance fields. In order to improve the performance of molding plastics, in recent years, researchers have tried to improve the comprehensive performance of molding plastics through the synergistic effect of modified resins and reinforcing fillers.

[0003] As an important thermosetting resin, amino resin is widely used in the preparation of molding materials due to its excellent hardness, heat resistance and chemical stability. However, traditional amino resins tend to produce a large shrinkage rate during the curing process, resulting in poor dimensional stability of the molding materials. In addition, the interface compatibility between amino resins and reinforcing fillers is low, which limits the improvement of the mechanical properties of molding materials. Therefore, how to reduce shrinkage, improve mechanical properties and dimensional stability by modifying amino resins has become an important research direction in the field of molding materials.

[0004] Corn stalks are a renewable biomass resource with abundant sources and low cost. They have gradually attracted wide attention due to their environmental friendliness and sustainability. As agricultural waste, the efficient use of corn stalks can not only reduce environmental pollution, but also provide a green and low-cost reinforcing filler for the materials industry. However, there are many limitations in the application of untreated corn stalks in amino molding compounds, mainly because of their strong chemical inertness on the surface, lack of active groups, and difficulty in forming an effective interface with the amino resin matrix, thus affecting the mechanical properties and dimensional stability of the molding compounds. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide an amino molding compound particle and a preparation method thereof, so as to solve the problem that the interface compatibility between the amino resin and the straw-reinforced filler is low, which limits the improvement of the mechanical properties of the molding compound.

[0006] Based on the above purpose, the present invention provides a method for preparing amino molding compound particles, comprising the following steps:

[0007] (1) Glycidyl methacrylate and polypropylene glycol bis(aminopropyl ether) are mixed, the temperature is raised to 75-85° C., and the mixture is stirred for reaction for 3-5 hours. The reaction product is added to petroleum ether, the precipitate is collected, and the precipitate is vacuum dried to obtain amino-terminated acrylic acid;

[0008] (2) adding urea to a 37 wt % formaldehyde solution, adjusting the pH to 8-9 with a sodium hydroxide solution, heating to 55-65° C., stirring and reacting for 20-40 min, then adjusting the pH to 4.8-5.5 with a formic acid solution, adding amino-terminated acrylic acid and urea, heating to 75-85° C., stirring and reacting for 50-70 min, then cooling to 55-65° C., adding urea, stirring for 20-40 min, adjusting the pH to 7.7-8.5 with a sodium hydroxide solution, and cooling to room temperature to obtain a modified amino resin;

[0009] (3) Cut corn stalks into small pieces, wash them with tap water and air-dry them naturally, crush the air-dried stalks with a grinder, sieve them through a 40-60 mesh sieve, and dry them to obtain stalk pellets, then add 5-20 g of the stalk pellets into a sulfuric acid solution, heat it to 40-50° C., stir it for 4-8 h, wash it with water, and dry it to obtain pretreated corn stalks;

[0010] (4) adding the pretreated corn straw to deionized water, ultrasonicating for 20-40 minutes, then adding L-cysteine, carbodiimide hydrochloride and N-hydroxysuccinimide, stirring for 20-40 minutes, then heating to 30-40° C., stirring for reaction for 2-4 hours, filtering, washing with water, and drying to obtain thiolated corn straw;

[0011] (5) Put the thiolated corn stalks and the modified amino resin into a kneader, knead them evenly, dry them, and grind them through a 10-30 mesh sieve to obtain amino molding compound particles.

[0012] Preferably, in step (1), the molar ratio of glycidyl methacrylate to polypropylene glycol bis(aminopropyl ether) is 1:1.

[0013] Preferably, the weight average molecular weight of the polypropylene glycol bis(aminopropyl ether) in step (1) is 500-2000;

[0014] Preferably, in step (1), the amount of petroleum ether added is 10 times the weight of polypropylene glycol bis(aminopropyl ether).

[0015] Preferably, in step (2), the weight ratio of urea, formaldehyde solution and amino-terminated acrylic acid is 50-80:80-130:5-15.

[0016] Preferably, the weight ratio of urea added sequentially in step (2) is 15-25:30-50:5.

[0017] Preferably, the concentration of the sodium hydroxide solution in step (2) is 20wt%-40wt%.

[0018] Preferably, the concentration of the formic acid solution in step (2) is 40-60 wt %.

[0019] Preferably, in step (3), the weight ratio of the straw particles to the sulfuric acid solution is 5-20:100-400; and the concentration of the sulfuric acid solution is 10wt%-20wt%.

[0020] Preferably, in step (4), the weight ratio of pretreated corn straw, deionized water, L-cysteine, carbodiimide hydrochloride and N-hydroxysuccinimide is 5-20:25-100:5-45:0.2-1:5-20.

[0021] Preferably, in step (5), the weight ratio of thiolated corn stover to modified amino resin is 5-20:80-120.

[0022] Furthermore, the present invention also provides an amino molding compound particle obtained by the above-mentioned preparation method of the amino molding compound particle.

[0023] Beneficial effects of the present invention:

[0024] The present invention provides an amino molding compound particle and a preparation method thereof. Through the synergistic effect of an amino resin modified by amino-terminated acrylic acid and thiolated corn stalks, the prepared molding compound has low shrinkage, high bending strength and high impact strength, exhibits excellent dimensional stability and mechanical properties, is suitable for fields requiring high precision and high strength, and has broad application prospects.

[0025] The amino resin modified by amino-terminated acrylic acid prepared by the present invention plays an important role in the molding compound. On the one hand, it can improve the crosslinking density of the amino resin and corn stalks and enhance the compatibility of the two; on the other hand, its internal longer ether chain structure can increase the flexibility of the material and relieve the internal stress concentration, thereby further improving the mechanical properties of the molding compound while maintaining a low shrinkage rate. In addition, the thiol-modified corn stalks form a dense crosslinked network structure with the modified amino resin through the thiol-ene click reaction, which significantly improves the bending strength and impact strength of the molding compound, and at the same time enhances the interface bonding force between the corn stalks and the amino resin. DETAILED DESCRIPTION

[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0027] Embodiment 1:

[0028] (1) 2.8 g of glycidyl methacrylate and 10 g of polypropylene glycol bis(aminopropyl ether) with a weight average molecular weight of 500 were mixed, the temperature was raised to 75° C., and the reaction was stirred for 3 h. The reaction product was added to 100 g of petroleum ether, the precipitate was collected, and vacuum dried at 55° C. for 20 h to obtain amino-terminated acrylic acid;

[0029] (2) adding 15 g of urea to 80 g of a 37 wt % formaldehyde solution, adjusting the pH to 8.1 with a 20 wt % sodium hydroxide solution, heating to 55° C., stirring and reacting for 20 min, then adjusting the pH to 4.8 with a 40 wt % formic acid solution, adding 5 g of amino-terminated acrylic acid and 30 g of urea, heating to 75° C., stirring and reacting for 50 min, then cooling to 55° C., adding 5 g of urea, stirring for 20 min, adjusting the pH to 7.7 with a 20 wt % sodium hydroxide solution, and cooling to room temperature to obtain a modified amino resin;

[0030] (3) Cut corn stalks into small pieces, clean them with tap water and air-dry them naturally, crush the air-dried stalks with a pulverizer, sieve them through a 40-mesh sieve, and place them in a blast dryer to dry them at 45° C. for 20 h to obtain stalk pellets; then add 5 g of the stalk pellets to 100 g of a 10 wt % sulfuric acid solution, heat it to 40° C., stir it for 4 h, wash it with water, and dry it at 55° C. for 20 h to obtain pretreated corn stalks;

[0031] (4) 5 g of pretreated corn straw was added to 25 g of deionized water, and ultrasonicated for 20 min. Then, 5 g of L-cysteine, 0.2 g of carbodiimide hydrochloride and 5 g of N-hydroxysuccinimide were added, and stirred for 20 min. The temperature was then raised to 30 ° C. and stirred for 2 h. The mixture was filtered, washed with water, and dried at 55 ° C. for 20 h to obtain thiolated corn straw.

[0032] (5) 5 g of thiolated corn stalks and 80 g of modified amino resin were placed in a kneader, kneaded and discharged uniformly, dried at 55° C. for 20 h, and then ground through a 10-mesh sieve to obtain amino molding compound particles.

[0033] Embodiment 2:

[0034] (1) 1.4 g of glycidyl methacrylate and 10 g of polypropylene glycol bis(aminopropyl ether) with a weight average molecular weight of 1000 were mixed, the temperature was raised to 80° C., and the mixture was stirred for reaction for 4 h. The reaction product was added to 100 g of petroleum ether, the precipitate was collected, and vacuum dried at 60° C. for 24 h to obtain amino-terminated acrylic acid;

[0035] (2) adding 20 g of urea to 105 g of a 37 wt % formaldehyde solution, adjusting the pH to 8.5 with a 30 wt % sodium hydroxide solution, heating to 60° C., stirring and reacting for 30 min, then adjusting the pH to 5.2 with a 50 wt % formic acid solution, adding 10 g of amino-terminated acrylic acid and 40 g of urea, heating to 80° C., stirring and reacting for 60 min, then cooling to 60° C., adding 5 g of urea, stirring for 30 min, adjusting the pH to 8.1 with a 30 wt % sodium hydroxide solution, and cooling to room temperature to obtain a modified amino resin;

[0036] (3) Cut corn stalks into small pieces, wash them with tap water and air dry them naturally, crush the air-dried stalks with a pulverizer, sieve them through a 50-mesh sieve, and dry them in a blast dryer at 50° C. for 24 hours to obtain stalk pellets; then add 10 g of the stalk pellets to 200 g of a 15 wt % sulfuric acid solution, heat it to 45° C., stir it for 6 hours, wash it with water, and dry it at 60° C. for 24 hours to obtain pretreated corn stalks;

[0037] (4) 10 g of pretreated corn straw was added to 50 g of deionized water, and ultrasonicated for 30 min. Then, 20 g of L-cysteine, 0.5 g of carbodiimide hydrochloride and 10 g of N-hydroxysuccinimide were added, and stirred for 30 min. The temperature was then raised to 35° C., and stirred for 3 h. The mixture was filtered, washed with water, and dried at 60° C. for 24 h to obtain thiolated corn straw.

[0038] (5) 10 g of thiolated corn stalks and 100 g of modified amino resin were placed in a kneader, kneaded and uniformly discharged, dried at 60° C. for 24 h, and then ground through a 20-mesh sieve to obtain amino molding compound particles.

[0039] Embodiment 3:

[0040] (1) 0.7 g of glycidyl methacrylate and 10 g of polypropylene glycol bis(aminopropyl ether) with a weight average molecular weight of 2000 were mixed, the temperature was raised to 85° C., and the reaction was stirred for 5 h. The reaction product was added to 100 g of petroleum ether, the precipitate was collected, and vacuum dried at 65° C. for 28 h to obtain amino-terminated acrylic acid;

[0041] (2) adding 25 g of urea to 130 g of a 37 wt % formaldehyde solution, adjusting the pH to 9 with a 40 wt % sodium hydroxide solution, heating to 65° C., stirring and reacting for 40 min, then adjusting the pH to 5.5 with a 60 wt % formic acid solution, adding 15 g of amino-terminated acrylic acid and 50 g of urea, heating to 85° C., stirring and reacting for 70 min, then cooling to 65° C., adding 5 g of urea, stirring for 40 min, adjusting the pH to 8.5 with a 40 wt % sodium hydroxide solution, and cooling to room temperature to obtain a modified amino resin;

[0042] (3) Cut corn stalks into small pieces, clean them with tap water and air-dry them naturally, crush the air-dried stalks with a pulverizer, sieve them through a 60-mesh sieve, and place them in a blast dryer to dry them at 55° C. for 28 hours to obtain stalk pellets; then add 20 g of the stalk pellets to 400 g of a 20 wt % sulfuric acid solution, heat it to 50° C., stir it for 8 hours, wash it with water, and dry it at 65° C. for 28 hours to obtain pretreated corn stalks;

[0043] (4) 20 g of pretreated corn straw was added to 100 g of deionized water, ultrasonicated for 40 min, then 45 g of L-cysteine, 1 g of carbodiimide hydrochloride and 20 g of N-hydroxysuccinimide were added, stirred for 40 min, then heated to 40° C., stirred for 4 h, filtered, washed with water, and dried at 65° C. for 28 h to obtain thiolated corn straw;

[0044] (5) 20 g of thiolated corn stalks and 120 g of modified amino resin were placed in a kneader, kneaded and uniformly discharged, dried at 65° C. for 28 h, and then ground through a 30-mesh sieve to obtain amino molding compound particles.

[0045] Comparative Example 1:

[0046] The difference between Comparative Example 1 and Example 2 is that the amino-terminated acrylic acid in step (2) is replaced by glycidyl methacrylate;

[0047] (1) adding 20 g of urea to 105 g of a 37 wt % formaldehyde solution, adjusting the pH to 8.5 with a 30 wt % sodium hydroxide solution, heating to 60° C., stirring and reacting for 30 min, then adjusting the pH to 5.2 with a 50 wt % formic acid solution, adding 10 g of glycidyl methacrylate and 40 g of urea, heating to 80° C., stirring and reacting for 60 min, then cooling to 60° C., adding 5 g of urea, stirring for 30 min, adjusting the pH to 8.1 with a 30 wt % sodium hydroxide solution, and cooling to room temperature to obtain a modified amino resin;

[0048] (2) Cut corn stalks into small pieces, wash them with tap water and air dry them naturally, crush the air-dried stalks with a pulverizer, sieve them through a 50-mesh sieve, and dry them in a blast dryer at 50° C. for 24 hours to obtain stalk pellets; then add 10 g of the stalk pellets to 200 g of a 15 wt % sulfuric acid solution, heat it to 45° C., stir it for 6 hours, wash it with water, and dry it at 60° C. for 24 hours to obtain pretreated corn stalks;

[0049] (3) 10 g of pretreated corn straw was added to 50 g of deionized water, and ultrasonicated for 30 min. Then, 20 g of L-cysteine, 0.5 g of carbodiimide hydrochloride and 10 g of N-hydroxysuccinimide were added, and stirred for 30 min. The temperature was then raised to 35° C., and stirred for reaction for 3 h. The mixture was filtered, washed with water, and dried at 60° C. for 24 h to obtain thiolated corn straw.

[0050] (4) 10 g of thiolated corn stalks and 100 g of modified amino resin were placed in a kneader, kneaded and uniformly discharged, dried at 60° C. for 24 h, and then ground through a 20-mesh sieve to obtain molding compound particles.

[0051] Comparative Example 2:

[0052] The difference between Comparative Example 2 and Example 2 is that the amino-terminated acrylic acid in step (2) is replaced by polypropylene glycol bis(aminopropyl ether) having a weight average molecular weight of 1000;

[0053] The specific steps are as follows:

[0054] (1) adding 20 g of urea to 105 g of a 37 wt % formaldehyde solution, adjusting the pH to 8.5 with a 30 wt % sodium hydroxide solution, heating to 60° C., stirring and reacting for 30 min, then adjusting the pH to 5.2 with a 50 wt % formic acid solution, adding 10 g of polypropylene glycol bis(aminopropyl ether) having a weight average molecular weight of 1000 and 40 g of urea, heating to 80° C., stirring and reacting for 60 min, then cooling to 60° C., adding 5 g of urea, stirring for 30 min, adjusting the pH to 8.1 with a 30 wt % sodium hydroxide solution, and cooling to room temperature to obtain a modified amino resin;

[0055] (2) Cut corn stalks into small pieces, wash them with tap water and air dry them naturally, crush the air-dried stalks with a pulverizer, sieve them through a 50-mesh sieve, and dry them in a blast dryer at 50° C. for 24 hours to obtain stalk pellets; then add 10 g of the stalk pellets to 200 g of a 15 wt % sulfuric acid solution, heat it to 45° C., stir it for 6 hours, wash it with water, and dry it at 60° C. for 24 hours to obtain pretreated corn stalks;

[0056] (3) 10 g of pretreated corn straw was added to 50 g of deionized water, and ultrasonicated for 30 min. Then, 20 g of L-cysteine, 0.5 g of carbodiimide hydrochloride and 10 g of N-hydroxysuccinimide were added, and stirred for 30 min. The temperature was then raised to 35° C., and stirred for reaction for 3 h. The mixture was filtered, washed with water, and dried at 60° C. for 24 h to obtain thiolated corn straw.

[0057] (4) 10 g of thiolated corn stalks and 100 g of modified amino resin were placed in a kneader, kneaded and uniformly discharged, dried at 60° C. for 24 h, and then ground through a 20-mesh sieve to obtain molding compound particles.

[0058] Comparative Example 3:

[0059] The difference between Comparative Example 3 and Example 2 is that: amino-terminated acrylic acid is not added in step (2);

[0060] The specific steps are as follows:

[0061] (1) adding 20 g of urea to 105 g of a 37 wt % formaldehyde solution, adjusting the pH to 8.5 with a 30 wt % sodium hydroxide solution, heating to 60° C., stirring and reacting for 30 min, then adjusting the pH to 5.2 with a 50 wt % formic acid solution, adding 40 g of urea, heating to 80° C., stirring and reacting for 60 min, then cooling to 60° C., adding 5 g of urea, stirring for 30 min, adjusting the pH to 8.1 with a 30 wt % sodium hydroxide solution, and cooling to room temperature to obtain an amino resin;

[0062] (2) Cut corn stalks into small pieces, wash them with tap water and air dry them naturally, crush the air-dried stalks with a pulverizer, sieve them through a 50-mesh sieve, and dry them in a blast dryer at 50° C. for 24 hours to obtain stalk pellets; then add 10 g of the stalk pellets to 200 g of a 15 wt % sulfuric acid solution, heat it to 45° C., stir it for 6 hours, wash it with water, and dry it at 60° C. for 24 hours to obtain pretreated corn stalks;

[0063] (3) 10 g of pretreated corn straw was added to 50 g of deionized water, and ultrasonicated for 30 min. Then, 20 g of L-cysteine, 0.5 g of carbodiimide hydrochloride and 10 g of N-hydroxysuccinimide were added, and stirred for 30 min. The temperature was then raised to 35° C., and stirred for reaction for 3 h. The mixture was filtered, washed with water, and dried at 60° C. for 24 h to obtain thiolated corn straw.

[0064] (4) 10 g of thiolated corn stalks and 100 g of amino resin were placed in a kneader, kneaded and uniformly discharged, dried at 60° C. for 24 h, and then ground through a 20-mesh sieve to obtain molding compound particles.

[0065] Comparative Example 4:

[0066] The difference between Comparative Example 4 and Example 2 is that the thiolated corn stover in step (5) is replaced with pretreated corn stover;

[0067] The specific steps are as follows:

[0068] (1) 1.4 g of glycidyl methacrylate and 10 g of polypropylene glycol bis(aminopropyl ether) with a weight average molecular weight of 1000 were mixed, the temperature was raised to 80° C., and the mixture was stirred for reaction for 4 h. The reaction product was added to 100 g of petroleum ether, the precipitate was collected, and vacuum dried at 60° C. for 24 h to obtain amino-terminated acrylic acid;

[0069] (2) adding 20 g of urea to 105 g of a 37 wt % formaldehyde solution, adjusting the pH to 8.5 with a 30 wt % sodium hydroxide solution, heating to 60° C., stirring and reacting for 30 min, then adjusting the pH to 5.2 with a 50 wt % formic acid solution, adding 10 g of amino-terminated acrylic acid and 40 g of urea, heating to 80° C., stirring and reacting for 60 min, then cooling to 60° C., adding 5 g of urea, stirring for 30 min, adjusting the pH to 8.1 with a 30 wt % sodium hydroxide solution, and cooling to room temperature to obtain a modified amino resin;

[0070] (3) Cut corn stalks into small pieces, wash them with tap water and air dry them naturally, crush the air-dried stalks with a pulverizer, sieve them through a 50-mesh sieve, and dry them in a blast dryer at 50° C. for 24 hours to obtain stalk pellets; then add 10 g of the stalk pellets to 200 g of a 15 wt % sulfuric acid solution, heat it to 45° C., stir it for 6 hours, wash it with water, and dry it at 60° C. for 24 hours to obtain pretreated corn stalks;

[0071] (4) 10 g of pretreated corn stalks and 100 g of modified amino resin were placed in a kneader, kneaded and discharged uniformly, dried at 60° C. for 24 h, and then ground through a 20-mesh sieve to obtain molding compound particles.

[0072] Performance Testing:

[0073] Preparation of molding compound: The molding compound particles prepared in the embodiment and the comparative example are uniformly filled into a mold for compression molding at a molding temperature of 160° C., a pressure of 30 MPa, and a time of 1 min / mm to obtain a molding compound.

[0074] Shrinkage test: According to the national standard GB13454-92, the molding shrinkage of the molding compound was measured. The results are shown in Table 1.

[0075] Bending strength measurement: The molding bending strength was measured according to the national standard GB9341 plastic bending test method. The results are shown in Table 1.

[0076] Impact strength measurement: According to the national standard GB1043 plastic cylindrical beam impact test method, the notched impact strength of the molding material was measured. The results are shown in Table 1.

[0077] Table 1 Performance test results

[0078]

[0079] Data Analysis:

[0080] It can be seen from the data of Examples 1-3 in Table 1 that the molding compound prepared from the amino molding compound particles provided by the present invention has low shrinkage, high bending strength and high impact strength, exhibits excellent dimensional stability and mechanical properties, is suitable for fields requiring high precision and high strength, and has broad application prospects.

[0081] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that after replacing amino-terminated acrylic acid with glycidyl methacrylate, the flexural strength and impact strength of the molding material are significantly reduced. This is mainly because after glycidyl methacrylate is cross-linked with the urea-formaldehyde network, the alkenyl group at the hydrophobic end will be wrapped inside the amino resin due to the hydrophobic effect, thereby reducing the degree of cross-linking with the thiolated corn stalks during the molding process, thereby causing the overall mechanical properties of the molding material to decrease.

[0082] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that after replacing amino-terminated acrylic acid with polypropylene glycol bis(aminopropyl ether), the flexural strength and impact strength of the molding material are significantly reduced. This is mainly because polypropylene glycol bis(aminopropyl ether) lacks cross-linking groups with thiolated corn stalks, which results in the internal network structure of the molding material being not tight enough, thereby significantly weakening its mechanical properties.

[0083] It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that the amino resin modified by amino-terminated acrylic acid can significantly improve the flexural strength and impact strength of the molding material, and has little effect on the shrinkage rate. This is mainly because, on the one hand, the amino resin modified by amino-terminated acrylic acid can increase the crosslinking density of the amino resin and corn straw in the molding material and improve the compatibility between the two. On the other hand, the longer internal ether chain can increase the flexibility of the material and relieve internal stress concentration, thereby further improving the mechanical properties of the molding material while maintaining a low shrinkage rate.

[0084] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that the thiolation of corn straw can significantly improve the flexural strength and impact strength of the molding compound. This is mainly because the thiolated corn straw can form crosslinks with the modified amino resin through a thiol-ene click reaction, thereby improving the compatibility between the corn straw and the amino resin.

[0085] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing amino molding compound particles, characterized in that: The following steps are involved: (1) Glycidyl methacrylate and polypropylene glycol bis(aminopropyl ether) are mixed, the temperature is raised to 75-85° C., and the mixture is stirred for reaction for 3-5 hours. The reaction product is added to petroleum ether, the precipitate is collected, and the precipitate is vacuum dried to obtain amino-terminated acrylic acid; (2) adding urea to a 37 wt % formaldehyde solution, adjusting the pH to 8-9 with a sodium hydroxide solution, heating to 55-65° C., stirring and reacting for 20-40 min, then adjusting the pH to 4.8-5.5 with a formic acid solution, adding amino-terminated acrylic acid and urea, heating to 75-85° C., stirring and reacting for 50-70 min, then cooling to 55-65° C., adding urea, stirring for 20-40 min, adjusting the pH to 7.7-8.5 with a sodium hydroxide solution, and cooling to room temperature to obtain a modified amino resin; (3) Cut corn stalks into small pieces, wash them with tap water and air-dry them naturally, crush the air-dried stalks with a grinder, sieve them through a 40-60 mesh sieve, and dry them to obtain stalk pellets, then add 5-20 g of the stalk pellets into a sulfuric acid solution, heat it to 40-50° C., stir it for 4-8 h, wash it with water, and dry it to obtain pretreated corn stalks; (4) adding the pretreated corn straw to deionized water, ultrasonicating for 20-40 minutes, then adding L-cysteine, carbodiimide hydrochloride and N-hydroxysuccinimide, stirring for 20-40 minutes, then heating to 30-40° C., stirring for reaction for 2-4 hours, filtering, washing with water, and drying to obtain thiolated corn straw; (5) Put the thiolated corn stalks and the modified amino resin into a kneader, knead them evenly, dry them, and grind them through a 10-30 mesh sieve to obtain amino molding compound particles. In the step (1), the molar ratio of glycidyl methacrylate to polypropylene glycol bis(aminopropyl ether) is 1:1; The weight average molecular weight of the polypropylene glycol bis(aminopropyl ether) in step (1) is 500-2000; In the step (2), the weight ratio of urea, formaldehyde solution and amino-terminated acrylic acid is 50-80:80-130:5-15; In the step (4), the weight ratio of the pretreated corn stalks, deionized water, L-cysteine, carbodiimide hydrochloride and N-hydroxysuccinimide is 5-20:25-100:5-45:0.2-1:5-20; In the step (5), the weight ratio of the thiolated corn stalks to the modified amino resin is 5-20:80-120.

2. The method for preparing amino molding compound particles according to claim 1, characterized in that: In the step (1), the amount of petroleum ether added is 10 times the weight of polypropylene glycol bis(aminopropyl ether).

3. The method for preparing amino molding compound particles according to claim 1, characterized in that: The weight ratio of urea added in the step (2) is 15-25:30-50:

5.

4. The method for preparing amino molding compound particles according to claim 1, characterized in that: In step (2), the concentration of the sodium hydroxide solution is 20wt%-40wt%, and the concentration of the formic acid solution is 40-60wt%.

5. The method for preparing amino molding compound particles according to claim 1, characterized in that: In the step (3), the weight ratio of the straw particles to the sulfuric acid solution is 5-20:100-400; and the concentration of the sulfuric acid solution is 10wt%-20wt%.

6. An amino molding compound particle, characterized in that: The amino molding compound particles are obtained by the preparation method of any one of claims 1 to 5.

Citation Information

Patent Citations

  • Material special for wood-like amino film plastics

    CN101864143A

  • Environment-friendly amino molding granule and production method thereof

    CN104419116A

  • In-situ reinforcing and toughening urea resin moulding compound and preparing method thereof

    CN105330801A

  • Rubber material and preparation method thereof

    CN108084528A

  • Delignificatin of biomass containing lignin and production of amino lignin aldehyde resins and carbohydrates

    US20110094678A1